2000
DOI: 10.1111/j.1365-2621.2000.tb16012.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Disulfide Bonds in Bovine β‐Lactoglobulin B Gels Set Thermally at Various pH

Abstract: To obtain information on forces important for maintenance of the structure of heat-set ␤-lactoglobulin gels, gels set from pure ␤-lactoglobulin at pH 3.0, 5.0, and 7.0 were solubilized in dissociating buffers, and solubilized material was characterized by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and size exclusion high performance liquid chromatography. The gel formed at pH 7.0 was largely soluble in urea (or SDS), and this gel seemed to be built from covalently linked soluble aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…For the development of protein gel, was used the WPI solution at 10% (w/w) and final pH was adjusted to 3.0 with 1 M of HCl (Merck, Germany). Heating WPI with high protein concentration (8e11%) and under acidic condi-tions can yield a gel stabilized by non-covalent bonding (Aymard, Nicolai, Durand, & Clark, 1999;Otte, Zakora, & Qvist, 2000). Electrical conductivity of the prepared WPI solutions ranged approximately from ca.…”
Section: Whey Protein Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the development of protein gel, was used the WPI solution at 10% (w/w) and final pH was adjusted to 3.0 with 1 M of HCl (Merck, Germany). Heating WPI with high protein concentration (8e11%) and under acidic condi-tions can yield a gel stabilized by non-covalent bonding (Aymard, Nicolai, Durand, & Clark, 1999;Otte, Zakora, & Qvist, 2000). Electrical conductivity of the prepared WPI solutions ranged approximately from ca.…”
Section: Whey Protein Solutionsmentioning
confidence: 99%
“…At acidic pH (far from the protein isoelectric point, which is ~5.2) and low ionic strength, a gel network form that is composed of fine strands in the order of nanometer in size (Ikeda & Morris, 2002;Kavanagh, Clark, & Ross-Murphy, 2000), where intermolecular covalent disulfide bonding is unlikely to occur (Aymard et al, 1999;Otte et al, 2000). WPI fine-stranded and transparent gels were produced at pH 3 after heating at 85 o C for 30 min.…”
Section: Whey Protein Gelationmentioning
confidence: 99%
“…Otte et al [81] studied the electrophoretic behavior of bovine CMP from rennet whey, using an untreated capillary under acidic, neutral and alkaline conditions. In rennet whey, CMP could be separated from whey proteins at low pH (70 mM phosphate buffer, pH 2.5), and some glycosylated CMP forms could be distinguished.…”
Section: Proteolysis In Milk and Cheesementioning
confidence: 99%
“…beta-lactoglobulin undergoes heatinduced structural changes, which involve the exposure of buried hydrophobic groups and thiol groups [34] . By contrast [32] provided evidence that polymerization of beta-lactoglobulin into a gel network does not occur via disulphide linkages. They explain that disulphide linkages occur initially during heating and the association of the soluble aggregates into a network occurs by non-covalent bonding which is a hydrophobic and/or hydrogen bond interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that the chaperone action of Alphacrystallin increased with increasing pH [30] . At lower pH values, the aggregation of beta-lactoglobulin occurs more by hydrophobic (nucleation-dependent) mechanisms since disulphide bond cleavage is highly pH dependent (i.e., it is reduced at lower pH values) [31,32] . Thus, it was proposed that even though alpha-crystallin's chaperone action is reduced at lower pH values, it should be able to prevent betalactoglobulin aggregation better at lower rather than at higher pH values.…”
Section: Discussionmentioning
confidence: 99%